2010
DOI: 10.1007/s10643-010-0403-3
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Early Childhood Educators: Children’s Interaction in Greek Child Care Centers

Abstract: Though quality in early childhood education and care has attracted last decades enormous research interest there is still not a unanimous agreement about its definition. Yet, almost all definitions attempted include interaction, group size, adult:child ratio and early childhood educators' level of education, as important indices of quality. Relationships are key resources for young children. There is agreement among researchers that the quality of caregiving by professional caregivers in child care centres has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 45 publications
(83 reference statements)
0
20
1
3
Order By: Relevance
“…Thus, research has indicated that Greek day care centres have large groups sizes and high adult-to-child ratios. Furthermore, Greek early childhood educators have been found to interact positively with children, but at the same time they exhibit detached and permissive behaviour (Rentzou 2010(Rentzou , 2011aRentzou and Sakellariou 2010). All these differences may explain partially the differences found in the level of burnout reported by the present sample, compared to research findings from other countries.…”
Section: Discussion and Recommendationscontrasting
confidence: 44%
See 1 more Smart Citation
“…Thus, research has indicated that Greek day care centres have large groups sizes and high adult-to-child ratios. Furthermore, Greek early childhood educators have been found to interact positively with children, but at the same time they exhibit detached and permissive behaviour (Rentzou 2010(Rentzou , 2011aRentzou and Sakellariou 2010). All these differences may explain partially the differences found in the level of burnout reported by the present sample, compared to research findings from other countries.…”
Section: Discussion and Recommendationscontrasting
confidence: 44%
“…As far as early childhood education and care in Greece is concerned we could argue that there is a dichotomy between care and education, which is found in other countries, too. Research data (Rentzou 2010(Rentzou , 2011aRentzou and Sakellariou 2010) have indicated that Greek day care centres provide low quality care and education and they emphasise on care rather than education. On the other hand, in kindergartens emphasis is placed on preschoolers' education.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Although no previous research has been conducted, to the best of our knowledge, in Cyprus examining teachers' beliefs and intensions about teacher/child interaction or the way Cypriot teachers interact with children, previous research in Greece (Rentzou and Sakellariou 2010a) has indicated that Greek early childhood educators interact positively with children, but at the same time they exhibit a detached and permissive approach and that they emphasise and prioritise aspects of children's care and not education. In general early childhood educators were observed to interact verbally with children mainly to give instructions and to control their behaviour and limited verbal interaction which elicited children's opinions and interests was observed.…”
Section: Discussionmentioning
confidence: 94%
“…In general, research suggests that early qualitative interaction between early childhood educators and children affects and predicts children's ensuing overall development (Leach et al 2008;Rudasill and Rimm-Kaufman 2009;Carl 2007;Fontaine et al 2006;Rentzou and Sakellariou 2010a).…”
Section: Teacher/child Interactionmentioning
confidence: 99%
“…There is a unanimous agreement among researchers that interaction between early childhood educators and children is an important index of quality early childhood education and care. Furthermore, the quality of caregiving in child care centres has been established as an important influence on various aspects of children's overall development (Carl, 2007;Fontaine, Dee Torre, Grafwallner, & Underhill, 2006;Leach et al, 2008;LoCasale-Crouch et al, 2007;Rentzou & Sakellariou, 2010a;Rudasill & Rimm-Kaufman, 2009).…”
Section: Teacher-child Interactionmentioning
confidence: 99%